Efficient continuous-wave, broadly tunable and passive Q-switching lasers based on a Tm3+:CaF2 crystal. (27th February 2018) - Liu, Jingjing; Zhang, Cheng; Zu, Yuqian; Fan, Xiuwei; Liu, Jie; Guo, Xinsheng; Qian, Xiaobo; Su, Liangbi
Abstract: Laser operations in the continuous-wave as well as in the pulsed regime of a 4 at.% Tm 3+ :CaF2 crystal are reported. For the continuous-wave operation, a maximum average output power of 1.15 W was achieved, and the corresponding slope efficiency was more than 64%. A continuous tuning range of about 160 nm from 1877–2036 nm was achieved using a birefringent filter. Using Argentum nanorods as a saturable absorber, the significant pulsed operation of a passively Q-switched Tm 3+ :CaF2 laser was observed at 1935.4 nm for the first time, to the best of our knowledge. A maximum output power of 385 mW with 41.4 µ J pulse energy was obtained under an absorbed pump power of 2.04 W. The present results indicate that the Tm 3+ :CaF2 lasers could be promising laser sources to operate in the eye-safe spectral region.